2015
DOI: 10.1089/apc.2015.0139
|View full text |Cite
|
Sign up to set email alerts
|

The HIV Care Cascade Measured Over Time and by Age, Sex, and Race in a Large National Integrated Care System

Abstract: HIV care cascades can evaluate programmatic success over time. However, methodologies for estimating cascade stages vary, and few have evaluated differences by demographic subgroups. We examined cascade performance over time and by age, sex, and race/ethnicity in Kaiser Permanente, providing HIV care in eight US states and Washington, DC. We created cascades for HIV+ members' age ≥13 for 2010-2012. We measured "linkage" (a visit/CD4 within 90 days of being diagnosed for new patients; ≥1 medical visit/year if e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 42 publications
5
60
1
Order By: Relevance
“…Males born in Honduras were also at increased risk compared with females born in Honduras, for retention in care only (aOR 2.22, 95% CI 1.31–3.78). Our finding of lower retention in care and viral suppression among males is consistent with the literature [36,42,43,44,45], although a few studies have found males to be more likely to be virally suppressed [44], or have found no differences by gender [35]. It is possible that males born in these countries traveled to the U.S. alone, either as migrant workers, or to work permanently in the U.S. to provide for a family member in their home country.…”
Section: Discussionsupporting
confidence: 93%
“…Males born in Honduras were also at increased risk compared with females born in Honduras, for retention in care only (aOR 2.22, 95% CI 1.31–3.78). Our finding of lower retention in care and viral suppression among males is consistent with the literature [36,42,43,44,45], although a few studies have found males to be more likely to be virally suppressed [44], or have found no differences by gender [35]. It is possible that males born in these countries traveled to the U.S. alone, either as migrant workers, or to work permanently in the U.S. to provide for a family member in their home country.…”
Section: Discussionsupporting
confidence: 93%
“…While many studies have found significant black-white disparities in ART use [2, 4, 6, 2123], some have found no racial disparities when examining specific populations, such as clinic attendees or those newly eligible for ART [3, 5, 24]. Regarding Hispanic-white disparities, many [2, 3, 6, 21, 22, 25], though not all [4, 23, 24], found no significant Hispanic-white difference in ART use. Across varying populations, most studies find black-white disparities in viral suppression [47, 21, 2528].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Hispanic-white disparities, many [2, 3, 6, 21, 22, 25], though not all [4, 23, 24], found no significant Hispanic-white difference in ART use. Across varying populations, most studies find black-white disparities in viral suppression [47, 21, 2528]. Only one recent analysis found no black-white differences in time to viral suppression among a large cohort of persons newly eligible for ART [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STTR treatment cascade provides a framework for research aimed at improving the delivery of services, care and outcomes of PLWH. There is substantial dropout across each cascade step, and it has been estimated that only ~19% of PLWH in the United States (US) are aware of their HIV diagnosis, engaged in care, on ART, and have an undetectable viral load (VL) [1], although more recent numbers suggest improvements [4, 5]. The development of effective approaches to increase HIV diagnoses and engage PLWH in subsequent steps of the treatment cascade could lead to earlier and sustained ART treatment resulting in viral suppression.…”
Section: Introductionmentioning
confidence: 99%